Diagnosis and Challenges of Polycystic Ovary Syndrome in Adolescence - Agapova, Sophia E.; Cameo, Tamara; Sopher, Aviva B.; Oberfield, Sharon E. (Seminars in Reproductive Medicine, 2014)
Although the diagnostic criteria for polycystic ovary syndrome (PCOS) have become less stringent over the years, determination of the minimum diagnostic features in adolescents is still an area of controversy. Of particular concern is that many of the features considered to be diagnostic for PCOS may evolve over time and change during the first few years after menarche. Nonetheless, attempts to define young women who may be at risk for development of PCOS is pertinent since associated morbidity such as obesity, insulin resistance, and dyslipidemia may benefit from early intervention. The relative utility of diagnostic tools such as persistence of anovulatory cycles, hyperandrogenemia, hyperandrogenism (hirsutism, acne, or alopecia), or ovarian findings on ultrasound is not established in adolescents. Some suggest that even using the strictest criteria, the diagnosis of PCOS may not valid in adolescents younger than 18 years. In addition, evidence does not necessarily support that lack of treatment of PCOS in younger adolescents will result in untoward outcomes since features consistent with PCOS often resolve with time. The presented data will help determine if it is possible to establish firm criteria which may be used to reliably diagnose PCOS in adolescents.
Keywords: polycystic ovary syndrome; polycystic ovarian morphology; type 2 diabetes mellitus